Evaluation of morphology, growth performance and sensory attributes of 4our Red HybridTilapia (Oreochromis Sp.)Strains. - Mohd Zharif Ramli (2017)
Deterioration of good characteristics in tilapia stocks causes the decline in its production yield. Current research investigated red hybrid tilapia strains by emphasising on physical, growth and taste characteristics which have the potential to be improved. Four red hybrid tilapia strains were produced by four different combinations; (i) ♂O.niloticus x ♀O.niloticus (A), (ii) ♂O.mossambicus x ♀O.mossambicus (B), (iii) ♂O.niloticus x ♀O.mossambicus (C) and (iv) ♂O.mossambicus x ♀O. niloticus (D). Fries were reared in 12 hapas (3.0 m x 2.0 m x 1.2 m) in earthen pond, fed 5% of their body weight with commercial feed (35- 40%Crude Protein) at stocking density of 10 individuals/m3 for 70 days. Twenty-three morphometric characteristics and 6 parameters of growth performance were evaluated concurrently. Meanwhile, sensory analysis of the fish was carried out after 4 months of being raised in the earthen pond. The morphometric data were analysed in allometric ratio followed by hierarchical cluster analysis. Morphometric and growth performance characteristics were analysed by analysis of variance (ANOVA).The results showed 9 characteristics which are body width (Bw1), distance from end of dorsal ray to 1st anal fin (D1daL), distance from caudal to anal fin (DcaL), body height (BH), pre-pectoral length (PCL), pre-pelvic length (PPL), pre-anal length (PAL), pre-orbital length (POL), pelvic fin length (PlvL) were found to be significantly different (p<0.05) between these strains. Hierarchical cluster analysis characterised these strains into 2 groups and 1 sub-group which inferred the variation between strains. Initial weight (Wi), Final weight (Wf), Relative Growth Rate (RGR), Feed Conversion Ratio (FCR), Specific Growth Rate (SGR) and Survival Rate (SR) were calculated. No statistical difference (p<0.05) between evaluated strains were found in these parameters. However, strain A had the highest score in Wf (19.63±0.69), RGR (2357.06±66.78), FCR (1.33±0.02) and SGR (4.57±0.03) in numerical data. Lowest mean values of growth performances were recorded on strain B which was Wf (17.77±0.98), RGR (2130.88±92.14), FCR (1.50±0.02) and SGR (4.43±0.06). Meanwhile, the growth performance of strains C and D were found to be at average mean value. SR was highly scored (>90%) in all strains with no statistical difference (p<0.05). Non- parametric data of sensory analysis were analysed by Kruskal-Wallis test. Generally, there is no significant difference (p>0.05) between attributes (taste, odour and juiciness) except for texture. These findings showed that unique characteristics distinguished between strains and combination of breeding effectively produced strains with good characteristics. Utilisation of ♀ O.niloticus is the key element for characteristics improvements in red hybrid tilapia strains.